Arabidopsis thaliana PRR7 Provides Circadian Input to the CCA1 Promoter in Shoots but not Roots - Nimmo, Hugh G.; Laird, Janet (Frontiers in Plant Science, 2021)
The core of the plant circadian clock involves multiple interlocking gene expression loops and post-translational controls along with inputs from light and metabolism. The complexity of the interactions is such that few specific functions can be ascribed to single components. In previous work we reported differences in the operation of the clocks in Arabidopsis shoots and roots, including the effects of mutations of key clock components. Here we have used luciferase imaging to study prr7 mutants expressing CCA1::LUC and GI::LUC markers. In mature shoots expressing CCA1::LUC, loss of PRR7 radically altered behaviour in light:dark cycles and caused loss of rhythmicity in constant light, but had little effect on roots. In contrast, in mature plants expressing GI::LUC, loss of PRR7 had little effect in light:dark cycles but in constant light increased the circadian period in shoots and reduced it in roots. We conclude that most or all of the circadian input to the CCA1 promoter in shoots is mediated by PRR7, and that loss of PRR7 has organ-specific effects. The results emphasize the differences in operation of the shoot and root clocks, and the importance of studying clock mutants in both light:dark cycles and constant light.